Intimate partner violence and associated factors among women during the COVID-19 pandemic in Ethiopia: a systematic review and meta-analysis - Alemu, Tewodros Getaneh; Tamir, Tadesse Tarik; Workneh, Belayneh Shetie; Mekonen, Enyew Getaneh; Ali, Mohammed Seid; Zegeye, Alebachew Ferede; Wassie, Mulugeta; Kassie, Alemneh Tadesse; Tekeba, Berhan; Gonete, Almaz Tefera; Techane, Masresha Asmare (Frontiers in Global Women's Health, 2024)
Background: During the COVID-19 pandemic, intimate partner violence has increased globally, but most notably in Africa. Conditions such as movement restrictions, staying home, and school closures increase the risk of domestic violence against women. Intimate partner violence is a violence demonstrated by an intimate partner against women including physical, sexual, and psychological violence. Thus, this research aims to identify factors contributing to Intimate partner violence among women during COVID-19. We searched over electronic databases, including PubMed, Google Scholar, CINAHL, Cochrane, and others. Two reviewers separately carried out the Joanna Briggs Institute search, study selection, critical appraisal, and data extraction. All ten studies included in this study; published in English, with publication dates before February 25, 2024. The Microsoft Excel checklist was used to extract the data, which were then exported to STATA 11. I 2, Funnel plots, and Egger's test were employed to measure heterogeneity and detect publication bias, respectively. A random effect model was used to estimate the pooled prevalence of intimate partner violence and associated factors among women during the COVID-19 pandemic.The meta-analysis includes a sample size of 6,280 women from ten articles. The pooled prevalence of intimate partner violence during COVID-19 pandemic was found to be 31.60% (95% CI: 21.10, 42.11) and significant factors were: partner alcohol use 1.93 (95% CI: 1.60, 2.23), income loss during COVID 19 9.86 (95% CI: 6.35, 15.70), partner illiterate education status 2.03 (95% CI: 1.57, 2.63), and decision making in the household 1.82 (95% CI: 1.33, 2.50). This systematic review and meta-analysis found preliminary evidence that intimate partner violence increased during the COVID-19 pandemic. The partner who has a history of alcohol use, women who were lost income during COVID-19, partner who has no formal education, and household decisions made by the husband alone were statistically significant factors for intimate partner violence during the COVID-19 pandemic. This implies that the health sector must play a significant role in providing women who are victims of violence with comprehensive health care, advocating about violence against women should be viewed as unacceptable, and improving literacy to minimize consequences of intimate partner violence among women.